Pengaruh Rasio Keuangan Terhadap Nilai Perusahaan Farmasi di BEI - Anjula Elbawati; Sari Rusmita; Haryono Haryono (LPMP Imperium, 2024)
The current economic situation has created fierce competition among companies to increase their value and appear attractive to investors. This study aims to determine the impact of financial ratios (liquidity, profitability, and solvency) on the value of pharmaceutical companies listed on the IDX. Multiple linear regression analysis methods were used in this study. The results indicated that liquidity positively and significantly affects firm value. In contrast, profitability and solvency have a negative and insignificant impact on firm value. Simultaneously, liquidity, profitability, and solvency collectively significantly influence firm value. Public interest statements This study is valuable for understanding how financial ratios affect the value of pharmaceutical companies listed on the IDX. By analyzing liquidity, profitability, and solvency ratios, this study helps investors and managers make better-informed decisions. Investors can evaluate financial health and growth potential, while managers can pinpoint areas that require improvement. This research is anticipated to enhance the transparency and efficiency of the Indonesian capital market, particularly in the pharmaceutical sector.